Comparative embryology and taxonomic considerations in Eriocaulaceae (Poales) - Coan, Alessandra Ike [UNESP]; Stützel, Thomas; Scatena, Vera Lucia [UNESP] (Wiley, 2012)
The genus concept within Eriocaulaceae is widely discussed because it is mainly based on a small number of floral characteristics of unknown functional and evolutionary significance. The aim of the present work is to comparatively study the embryology of representatives of most genera of Eriocaulaceae to identify relevant features that might aid in circumscribing them. In Eriocaulaceae, the uniformity of the embryological characteristics makes it difficult to interpret the existing relationships among the genera. Some embryological characteristics, especially those related to the number of microsporangia, are shown to be unstable and restricted to Paepalanthoideae. The unique pollen morphology may be related to mechanical processes to accommodate the increase in volume after early formation of the pollen wall and may indicate a relationship to an inaperturate ancestor. The placentation, formerly stated to be axile, is more likely to be central due to protusions of the locular base. The shape of the proximal region of the megagametophyte may be responsible for the formation of the antipodal cyst. The seed coat structure is uniform in origin and is a consistent taxonomic characteristic of the family. A review of Eriocaulaceae is necessary, in which additional morphological and anatomical characteristics should be considered and combined. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Anther; Eriocauloideae; Ovule; Paepalanthoideae; Seed; Eriocaulaceae; Poales